2010
DOI: 10.1155/2011/735297
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Frequency Electroacupuncture Improves Insulin Sensitivity in Obese Diabetic Mice through Activation of SIRT1/PGC‐1α in Skeletal Muscle

Abstract: Electroacupuncture (EA) has been observed to reduce insulin resistance in obesity and diabetes. However, the biochemical mechanism underlying this effect remains unclear. This study investigated the effects of low-frequency EA on metabolic action in genetically obese and type 2 diabetic db/db mice. Nine-week-old db/m and db/db mice were randomly divided into four groups, namely, db/m, db/m + EA, db/db, and db/db + EA. db/m + EA and db/db + EA mice received 3-Hz electroacupuncture five times weekly for eight co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 44 publications
2
58
0
Order By: Relevance
“…Low-frequency EA is applied more frequently for the treatment of insulin resistance with beneficial results (25,29,30). In the current study, we tested various frequencies and found EA with 3 Hz and 15 Hz reduced blood glucose; whereas neither 1 Hz nor 100 Hz had any hypoglycemic effect in mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Low-frequency EA is applied more frequently for the treatment of insulin resistance with beneficial results (25,29,30). In the current study, we tested various frequencies and found EA with 3 Hz and 15 Hz reduced blood glucose; whereas neither 1 Hz nor 100 Hz had any hypoglycemic effect in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown EA at CV4 and CV12 with 15 Hz reduced plasma glucose concentration in rats with or without hyperglycemia (9); using the same EA method, Ishizaki et al (25) reported glucose tolerance was improved and insulin sensitivity was enhanced during EA in diabetic Goto-Kakizaki rats. With 3 Hz EA at CV4 and ST36, Liang et al (30) reported a reduction of fasting blood glucose after 8 wk of treatment in obese diabetic mice, an effect mediated via improvement in insulin sensitivity. Our findings were consistent with findings reported in the literature; however, we explored EA at more frequencies and different locations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of acupuncture on obesity has been investigated mainly in rats, with the exception of a recent study on mice. 51 …”
Section: Animal Studiesmentioning
confidence: 99%